Impact of Service Quality dimension of Commercial Banks on Customer in Nepal - Shrestha, Ranu Maiya (Pravaha, 2020)
Commercial bank service quality dimensions and customer satisfaction are related with each other. Customer satisfaction play significant role for the success of bank. A structured questionnaire with 5 point Likert scale has been used to collect the data by conducting field survey. The sample size is 144 and chosen on a convenient basis. Data has been analyzed by using statistical tools like mean and Correlation Coefficient. The result revealed that service quality dimensions like such as tangibility, reliability, assurance, empathy, and responsiveness have significantly and positively correlated on customer satisfaction of commercial bank in Nepal.